2023
DOI: 10.1007/s00011-023-01750-y
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of TRPA1 expression and function by Th1 and Th2-type inflammation in human A549 lung epithelial cells

Abstract: Background Transient Receptor Potential Ankyrin 1 (TRPA1) is a cation channel that mediates pain, itch, cough, and neurogenic inflammation in response to pungent compounds such as acrolein in cigarette smoke. TRPA1 is also activated by endogenous factors and promotes inflammation in asthma models. We have recently shown that TRPA1 is upregulated by inflammatory cytokines in A549 human lung epithelial cells. Here, we explored the effects of Th1 and Th2-type inflammation on TRPA1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…rodentium infection [ 43 ]. Additionally, it has been shown that the neutrophil-recruiting chemokine CXCL6 is upregulated by TRPA1 signaling [ 53 ], supporting regulation of this chemokine within the colon in a TRP channel dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…rodentium infection [ 43 ]. Additionally, it has been shown that the neutrophil-recruiting chemokine CXCL6 is upregulated by TRPA1 signaling [ 53 ], supporting regulation of this chemokine within the colon in a TRP channel dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…37 TRPA1 has thus been suggested to mediate airway inflammation raising the possibility that it could be a molecular target for asthma. 38…”
Section: Trp Channelsmentioning
confidence: 99%
“…When activated, TRPA1 sets off signaling pathways that signal the body to impending dangers, initiating defensive measures such as the release of inflammatory mediators and neuropeptides. Additionally, TRPA1 regulates epithelial barrier integrity, modulates secretion, and coordinates protective responses to preserve the function of the epithelial barrier and safeguard against potential hazards (Brierley et al, 2009;Luostarinen et al, 2023).…”
Section: Transient Receptor Potentialmentioning
confidence: 99%
“…These enzymes catalyze the production of reactive oxygen species (ROS), including superoxide and hydrogen peroxide, in response to microbial challenges (van der Vliet et al, 2018). Specifically, DUOX2/DUOXA2 serve as the primary hydrogen peroxide (H 2 O 2 ) producing system in the human colorectal mucosa and ileum (highest expression), releasing substantial quantities of H 2 O 2 from the epithelial layer into the gut lumen as part of the innate immune response (Macfie et al, 2014;Shu et al, 2023). The H 2 O 2 produced by epithelial cells acts as a defense mechanism, limiting microbial colonization and exhibiting toxicity against pathogens.…”
Section: Host-microbiota Crosstalk Epithelial Interactionsmentioning
confidence: 99%
See 1 more Smart Citation